Telerehabilitation Clinical and Vocational Applications for Assistive Technology: Research, Opportunities, and Challenges - Mark R. Schmeler; Richard M. Schein; Michael McCue; Kendra Betz (International Journal of Telerehabilitation)
Rehabilitation service providers in rural or underserved areas are often challenged in meeting the needs of their complex patients due to limited resources in their geographical area. Recruitment and retention of the rural clinical workforce are beset by the ongoing problems associated with limited continuing education opportunities, professional isolation, and the challenges inherent in coordinating rural community healthcare. People with disabilities who live in rural communities also face challenges accessing healthcare. Traveling long distances to a specialty clinic for necessary expertise may be troublesome due to inadequate or unavailable transportation, disability specific limitations, and financial limitations. Distance and lack of access are just two threats to quality of care that now being addressed by the use of videoconferencing, information exchange, and other telecommunication technologies that facilitate telerehabilitation. This white paper illustrates and summarizes clinical and vocational applications of telerehabilitation. We provide definitions related to the fields of telemedicine, telehealth, and telerehabilitation, and consider the impetus for telerehabilitation. We review the telerehabilitation literature for assistive technology applications; pressure ulcer prevention; virtual reality applications; speech-language pathology applications; seating and wheeled mobility applications; vocational rehabilitation applications; and cost effectiveness. We then discuss external telerehabilitation influencers, such as the positions of professional organizations. Finally, we summarize clinical and policy issues in a limited context appropriate to the scope of this paper. Keywords: Telerehabilitation, Telehealth, Telemedicine, Telepractice